Paediatric actinomycosis: a 16-year, single-institution retrospective review of cases - Chew, Siu-Jun (2024)
Aim: Actinomycosis is a rare subacute to chronic granulomatous infection which can mimic other infectious or malignant diseases. This study examined the epidemiology and treatment outcome of actinomycosis in children. Methods: A retrospective study on children admitted for actinomycosis in a tertiary paediatric hospital in Singapore, from January 2004 to December 2020. Clinical profile, therapeutic interventions and outcomes were examined. Results: A total of 10 patients were identified; 7 were female. The median age at first presentation was 9.8 years (range 4.7–15.7). The most common presenting symptom was fever (n = 6, 60%), followed by facial or neck swelling (n = 3, 30%) and ear pain (n = 3, 30%). Actinomycosis occurred predominantly in the orocervicofacial region (n = 6, 60%). Four patients (40%) had preceding dental infections in the form of dental caries or gingivitis. One patient had poorly controlled insulin-dependent diabetes mellitus. Actinomycosis was confirmed via culture in four patients, histopathology in four patients and both methods in two patients. All except one patient (n = 9, 90%) underwent surgical procedures. All patients received ampicillin or amoxicillin/clavulanate or other beta-lactams, for a median duration of 6.5 months (range 1.5–14). Complications included osteomyelitis (n = 4, 40%), mastoiditis (n = 2, 20%), brain abscess (n = 1, 10%) and recurrent neck abscess (n = 1, 10%). There was no mortality and all patients achieved complete resolution. Conclusions: Paediatric actinomycosis was rare in our 16-year review, but had a high complication rate. It can occur in immunocompetent patients, and dental infection was the predominant risk factor identified. Prognosis was excellent after surgical intervention and appropriate antimicrobial therapy.